(untitled) (The Review of Diabetic Studies, 2025)
Background: The management of diabetes mellitus and its complications presents a significant healthcare challenge in Saudi Arabia, particularly given the complex interplay between socioeconomic factors and treatment outcomes. While previous studies have examined clinical aspects of diabetes management, the relationship between social determinants, treatment adherence, and health outcomes remains understudied in the Saudi context. Objective: This study employs Partial Least Squares Structural Equation Modeling (PLS-SEM) to analyze the complex relationships between socioeconomic factors, treatment adherence, and diabetes complications among patients in Al-Ahsa Governorate, Saudi Arabia. Through three progressive models, we examine how demographic characteristics and treatment compliance influence health outcomes. Methods: We conducted a cross-sectional study (n=X) using a comprehensive survey instrument. Three PLS-SEM models were developed: (1) a basic model examining direct effects of demographics and treatment adherence on complications, (2) a mediation model incorporating treatment adherence as a mediator, and (3) a comprehensive model including complications severity as an additional construct. The models were evaluated using standard fit indices, path coefficients, and comparative metrics. Results: Demographic factors showed significant direct effects on complications (β=-0.273, p<0.05) and treatment adherence (β=0.397, p<0.05). Treatment adherence demonstrated a substantial negative relationship with complications (β=-0.401, p<0.05). Model comparison revealed that the basic model provided the best fit (BIC=-119.040, Akaike weight=0.960). Notably, socioeconomic factors significantly influenced complications severity (β=-0.407, p<0.001) in the comprehensive model. Conclusions: Our findings reveal significant associations between socioeconomic factors, treatment adherence, and diabetes complications in Saudi Arabia. The multi-model approach demonstrates that while demographic characteristics directly influence health outcomes, treatment adherence plays a crucial mediating role. These results suggest the need for targeted interventions that consider both social determinants and clinical factors in diabetes management.